PENGETAHUAN KANKER SERVIKS PADA WUS (WANITA USIA SUBUR) DI PUSAT STUDI WANITA UNIPDU JOMBANG - Retnowuni, Arifa; Zuliani, Zuliani; Lindayani, Athi’; Qomariana, Anna (Jurnal EDUNursing, 2024)
Cervical cancer is one of the types of cancer that is most often suffered by women, not only in Indonesia but also throughout the world with the second largest number suffered by women in Indonesia, after breast cancer, in terms of the number of incidents or cases as well as the death rate. The aim of this research is to determine knowledge about cervical cancer in WUS (women of childbearing age) at the Unipdu Jombang Women's Study Center. The type of research used in this research is descriptive which is carried out to determine the value of the independent variable. This research was conducted at the Unipdu Jombang Women's Study Center. The population in this study were all women of childbearing age who came to visit the Unipdu Jombang women's study center event. The sample in this study was a total sampling of 54 people. The instrument used was a questionnaire regarding knowledge of cervical cancer. Results: almost half of them were early elderly as many as 25 respondents (46.3%) and late adults as many as 20 respondents (37.1%), and most of them had tertiary education as many as 32 respondents (59.3%), and the knowledge category was 31. respondents (57.4%). Based on the results of research carried out describing the level of knowledge of women of childbearing age about cervical cancer at the Unipdu Jombang Women's Study Center, most of them are still in the poor category. Therefore, there is a need to provide education to women of childbearing age about cervical cancer and attitudes towards early prevention with pap smear examinations. Keywords: Knowledge, Cervical cancer, Women's Study Center